2019
DOI: 10.1002/mame.201900467
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of PET Nano‐Porous Luminescence Fibers for Fluorescence‐Indicating to Acid Gases

Abstract: This work describes the fluorescence‐indicating function to trace acid gases of polyethylene terephthalate (PET) nano‐porous luminescence fibers (PNPLFs) through the analysis of correlation between the concentration of acid gas and fluorescence intensity of organic rare earth complexes dispersed uniformly in the PET nano‐porous structured fibers. The porous structure and large specific surface area of the PET nano‐fibers prepared through electrospinning technology offer the strong adhesive force and good absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…[38] The results showed that H + could catalyze the ligand, and the coordination mode of BTA with rare earth ions changed from the original chelating bidentate coordination to monodentate coordination mode, which reduced the energy transfer efficiency between the ligand and rare earth ions. [39]…”
Section: Acid Rain Detection Mechanismmentioning
confidence: 99%
“…[38] The results showed that H + could catalyze the ligand, and the coordination mode of BTA with rare earth ions changed from the original chelating bidentate coordination to monodentate coordination mode, which reduced the energy transfer efficiency between the ligand and rare earth ions. [39]…”
Section: Acid Rain Detection Mechanismmentioning
confidence: 99%
“…When the fibers are used in medical products, direct γ-ray disinfection will not destroy the physical properties and stability of the fibers. 10 The excellent properties of PET fibers enable it to be widely used in industry, agriculture, aerospace, masks, and other fields. 11−14 In antibacterial PET fibers, the antibacterial agent used determines the preparation method and the antibacterial effect of antibacterial fibers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More importantly, PET fibers have the capacity to resist γ-rays. When the fibers are used in medical products, direct γ-ray disinfection will not destroy the physical properties and stability of the fibers . The excellent properties of PET fibers enable it to be widely used in industry, agriculture, aerospace, masks, and other fields. …”
Section: Introductionmentioning
confidence: 99%
“…With the gradual development of chemical industry, a large number of polluted gases are produced, which are discharged into the atmosphere and endanger people's health 1–3 . Acid gases (such as HCl, TFA, FA and SO 2 are widely used in all walks of life) account for a large proportion of harmful gases 4 . However, it is necessary to take convenient precautions in the gas state, because the gas is colorless, and it will quickly spread undetected in case of leakage 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the methods for monitoring acid gases, nano‐fluorescent materials show obvious advantages due to their large specific surface area and high adsorption capacity. For example, Chen et al 4 used polyethylene terephthalate (PET) to prepare nano‐porous luminescent fiber PNPLFs by electrospinning. Porous structure and large specific surface area endowed PNPLFs with strong adhesion to acid gas and good absorption efficiency.…”
Section: Introductionmentioning
confidence: 99%